Characterization of the Porous Micro-Arc Coatings Containing Boehmite Nanoparticles; AIP Conference Proceedings; Vol. 2051 : Advanced Materials with Hierarchical Structure for New Technologies and Reliable Structures 2018 (AMHS’18) - Chebodaeva V. V. Valentina Vadimovna; Sedelnikova M.; Gnedenkov S.; Sinebryukhov S.; Egorkin V.; Sharkeev Yu. P. Yury Petrovich (2018, 2018)
Title screen